1993
DOI: 10.1111/j.1651-2227.1993.tb12878.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between thermoregulation and the control of respiration in infants: possible relationship to sudden infant death

Abstract: In summary, there is evidence that developmental changes in respiratory control and in thermoregulation have effects upon each other. Theoretically, such effects could give rise to failure of the respiratory system and there is some circumstantial evidence to support the concept that on occasions such interactions may be of importance in sudden unexpected death in infancy. Future research in this area should focus on the nature of the interactions between thermoregulation and respiration, and on the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 13 publications
(7 reference statements)
1
38
1
Order By: Relevance
“…2 Although the mechanism of such an association remains unclear, the reported effects of the thermal environment on respiratory pattern suggest that, at least in some subjects, the mechanism may involve an interaction between thermoregulation and respiratory control. 3 In this context the head, as the site of about 40% of heat production and up to 85% of heat loss for the infant in bed, may be particularly vulnerable to the effects of thermal stress. 4 In two studies an excess incidence of head covering was found in infants who died from SIDS compared with matched controls,5 6 and in animal studies relatively small changes in brain temperature have been shown to have potentially major effects on the control of respiration.7 Thus factors which increase the resting metabolic rate might have a significant influence on respiratory control both by a 'feed forward' effect of increased carbon dioxide production (which may directly affect respiratory drive) and by an effect on cerebral temperature, particularly under conditions (for example a prone sleeping position, head covering) in which the ability to lose heat from the head might be compromised.3 6 7 The change in metabolic rate over the first three months after birth, which, when expressed in terms of heat loss for each unit of surface area amounts to an increase of over 50%, might be expected to put infants aged 3 months at a higher risk of the adverse effects of a warm environment than younger infants.8 In the Avon study the risk of SIDS was increased by the presence of heavy wrapping only for those aged more than 70 days.…”
mentioning
confidence: 99%
“…2 Although the mechanism of such an association remains unclear, the reported effects of the thermal environment on respiratory pattern suggest that, at least in some subjects, the mechanism may involve an interaction between thermoregulation and respiratory control. 3 In this context the head, as the site of about 40% of heat production and up to 85% of heat loss for the infant in bed, may be particularly vulnerable to the effects of thermal stress. 4 In two studies an excess incidence of head covering was found in infants who died from SIDS compared with matched controls,5 6 and in animal studies relatively small changes in brain temperature have been shown to have potentially major effects on the control of respiration.7 Thus factors which increase the resting metabolic rate might have a significant influence on respiratory control both by a 'feed forward' effect of increased carbon dioxide production (which may directly affect respiratory drive) and by an effect on cerebral temperature, particularly under conditions (for example a prone sleeping position, head covering) in which the ability to lose heat from the head might be compromised.3 6 7 The change in metabolic rate over the first three months after birth, which, when expressed in terms of heat loss for each unit of surface area amounts to an increase of over 50%, might be expected to put infants aged 3 months at a higher risk of the adverse effects of a warm environment than younger infants.8 In the Avon study the risk of SIDS was increased by the presence of heavy wrapping only for those aged more than 70 days.…”
mentioning
confidence: 99%
“…22,24 Therefore, it has been suggested that thermal stress, with or without moderate increases in body temperature, can result in fatal disruption of vital systems among infants predisposed to SIDS. 1,25 It has been proposed that congenital or acquired anatomic abnormalities in brainstem centers regulating respiratory or cardiovascular stability could represent the underlying defects that render SIDS infants susceptible to death resulting from heat stress. 26 Our reasoning in assuming that a substantial number of infants at risk for SIDS experienced significant heat stress is as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The primary evidence for this comes from epidemiological studies. These studies have found increased environmental temperature and/or history of heavy sweating in association with some SIDS cases (6,26, 27). Despite this, the potential physiological mechanisms linking heat stress to SIDS are unclear.…”
mentioning
confidence: 97%
“…It has been suggested that thermal stress with or without actual increase in body temperature (T B ) may be causal in many SIDS cases (6,12). The primary evidence for this comes from epidemiological studies.…”
mentioning
confidence: 99%